Role of ethno-phytomedicine knowledge in healthcare of COVID-19: advances in traditional phytomedicine perspective - Md Nasir Ahmed; Kerry Hughes (Beni-Suef University Journal of Basic and Applied Sciences, 2022)
Abstract Background Since the outbreak of the COVID-19 virus, ethnomedicinal plants have been used in diverse geographical locations for their purported prophylactic and pharmacological effects. Medicinal plants have been relied on by people around the globe for centuries, as 80% of the world’s population rely on herbal medicines for some aspect of their primary health care needs, according to the World Health Organization. Main body This review portrays advances in traditional phytomedicine by bridging the knowledge of ethno-phytomedicine and COVID-19 healthcare. Ethnomedicinal plants have been used for symptoms related to COVID-19 as antiviral, anti-infective, anti-inflammatory, anti-oxidant, antipyretic, and lung–gut immune boosters. Traditionally used medicinal plants have the ability to inhibit virus entry and viral assembly, bind to spike proteins, membrane proteins, and block viral replications and enzymes. The efficacy of traditional medicinal plants in the terms of COVID-19 management can be evaluated by in vitro, in vivo as well as different in silico techniques (molecular docking, molecular dynamics simulations, machine learning, etc.) which have been applied extensively to the quest and design of effective biotherapeutics rapidly. Other advances in traditional phytomedicines against COVID-19 are controlled clinical trials, and notably the roles in the gut microbiome. Targeting the gut microbiome via medicinal plants as prebiotics is also found to be an alternative and potential strategy in the search for a COVID-19 combat strategy. Conclusions Since medicinal plants are the sources of modern biotherapeutics development, it is essential to build collaborations among ethnobotanists, scientists, and technologists toward developing the most efficient and the safest adjuvant therapeutics against the pandemic of the twenty-first century, COVID-19.